Broad band temperature independent photonic crystal based optical filter with response in visible wavelength range. (7th March 2019) - Razi, Sepehr; Ghasemi, Fatemeh
Abstract: A new photonic crystal-based wide band (⩾200 nm) filter/mirror with a response in the visible frequency range is proposed. Alternating layers of Si–Ge and SiO2 slabs are considered as the main building blocks of the crystal. Having inserted stacks of the SiO2 /TiO2 unit cells inside the crystal, the alterations of the optical features of the ideal crystal can be explored. The number of defects, crystal temperature, light incident angle and the polarization of the light are considered as the controlling parameters for tuning the crystal optical characteristics. Investigating the dependencies systematically, it is shown that both the ideal and defective crystals have unique temperature independent features. More interestingly, the proposed crystals have an almost similar response for TE and TM polarizations. However, the light incident angle is a very effective factor for controlling not only the photonic band gap interval, but also for tuning the defect layer(s) induced resonant modes. Due to their 100% reflectivity in ~450–650 nm, simplicity in fabrication (limited number of layers and reasonable sizes), temperature independency (in 50 °C–300 °C) and comfortable tunability, the proposed structures might be interesting in photonic technology for manufacturing wide-band filters/mirrors.